2008
DOI: 10.1016/j.cell.2008.06.025
|View full text |Cite
|
Sign up to set email alerts
|

The GET Complex Mediates Insertion of Tail-Anchored Proteins into the ER Membrane

Abstract: SummaryTail-anchored (TA) proteins, defined by the presence of a single C-terminal transmembrane domain (TMD), play critical roles throughout the secretory pathway and in mitochondria, yet the machinery responsible for their proper membrane insertion remains poorly characterized. Here we show that Get3, the yeast homolog of the TA-interacting factor Asna1/Trc40, specifically recognizes TMDs of TA proteins destined for the secretory pathway. Get3 recognition represents a key decision step, whose loss can lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
706
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 483 publications
(749 citation statements)
references
References 53 publications
30
706
1
1
Order By: Relevance
“…Deletions of ER-resident Get2 (functional mammalian homologue CAML 60 ), cytosolic chaperone Get3 (mammalian homologue TRC40 16 ), the chaperone-interacting protein Sgt2 (mammalian homologue SGTA 61 ), and/or the ER-resident Get1 (mammalian homologue WRB 62 ) led to the formation of cytosolic aggregates, indicating the involvement of the GET pathway. Similar aggregates were observed under the same experimental conditions for the tail anchors of Ysy6 and Sec22, which were previously identified as GET pathway targets using the same phenotypic assay 17,19 . Note that there is no increase in the level of cytosolic aggregates in the Get2∆/Get1∆ strain over that observed in the Get2∆ strain, in line with the observation that Get1 is unable to insert in the ER in a Get2∆ background 63 .…”
Section: Investigation Of Tail Anchor Targeting Pathways That May Regsupporting
confidence: 61%
See 3 more Smart Citations
“…Deletions of ER-resident Get2 (functional mammalian homologue CAML 60 ), cytosolic chaperone Get3 (mammalian homologue TRC40 16 ), the chaperone-interacting protein Sgt2 (mammalian homologue SGTA 61 ), and/or the ER-resident Get1 (mammalian homologue WRB 62 ) led to the formation of cytosolic aggregates, indicating the involvement of the GET pathway. Similar aggregates were observed under the same experimental conditions for the tail anchors of Ysy6 and Sec22, which were previously identified as GET pathway targets using the same phenotypic assay 17,19 . Note that there is no increase in the level of cytosolic aggregates in the Get2∆/Get1∆ strain over that observed in the Get2∆ strain, in line with the observation that Get1 is unable to insert in the ER in a Get2∆ background 63 .…”
Section: Investigation Of Tail Anchor Targeting Pathways That May Regsupporting
confidence: 61%
“…6, with the emerging view that the overall hydropathy of the TMD plays an important role in determining pathway specificity 48 . From high to low overall hydropathy, the tail anchor can be targeted to the ER by the classical SRP pathway 13 , the Sec62/63 pathway 14 , the GET/TRC40 pathway [15][16][17][18][19][20][21][22] , more general chaperones [23][24][25] , or spontaneous insertion 27 . For all of these pathways, the Sec61 translocon likely plays either an essential or important role (even for spontaneous insertion).…”
Section: Investigation Of Tail Anchor Targeting Pathways That May Regmentioning
confidence: 99%
See 2 more Smart Citations
“…The ATPase Get3 was the first protein identified directly involved in TA targeting and is part of the Get pathway (now known as Guided Entry of Tail-anchored proteins) that also contains the ER membrane proteins Get1/2 and the putative ribosome receptor proteins Get4/5 (3)(4)(5)(6)(7). Multiple studies have shown that Get3 binds directly to the hydrophobic tail-anchors and, in conjunction with ribosome and endoplasmic reticulum (ER) factors, utilizes an ATP cycle to bind and then release TA proteins at the ER membrane.…”
mentioning
confidence: 99%